Race, ethnicity, and the use of regional anesthesia in cancer patients undergoing open abdominal surgery: A single-center retrospective cohort study - Owusu-Agyemang, Pascal; Feng, Lei; Porche, Vivian H.; Williams, Uduak U.; Cata, Juan P. (Frontiers in Medicine, 2022)
Background: Where applicable, regional anesthesia has been shown to be superior to opioid or non-opioid analgesic modalities alone. However, some studies have shown ethnic-based disparities in the use of regional anesthesia in patients undergoing surgical procedures. In this study of patients who had undergone major oncologic surgery, our main objective was to compare the use of regional anesthesia in patients of different ethnicities to its use in non-Hispanic White patients. Methods: A retrospective review of adults who had undergone major open abdominal surgical procedures between 2016 and 2021 was performed. Logistic regression models were used to assess the association between baseline patient characteristics and the use of regional anesthesia. Results: A total of 4791 patients were included in the analysis. The median age was 60.5 years [interquartile range, 49, 69], the majority were female (65 %), and of American Society of Anesthesiologists Physical Status Class 3 (94.7 %). Regional anesthesia was used in 2652 patients (55.4 %) and was not associated with race or ethnicity (p = 0.287). Compared to White patients, the odds of regional anesthesia use in other racial/ethnic groups were: Asian (odds ratio (OR) 0.851 [95 % confidence interval (CI), 0.660 to 1.097]; p = 0.2125), Black/African American (OR 0.807 [95 % CI, 0.651 to 1.001]; p = 0.0508), Hispanic/Latino (OR 0.957 [95 % CI, 0.824 to 1.154]; p = 0.7676), Other race (OR 0.957 [95 % CI, 0.627 to 1.461]; p = 0.8376). In the multivariable analysis, age (OR 0.995 [95 % CI, 0.991 to 1.000]; p = 0.0309) and female gender (OR 1.231 [95 % CI, 1.090 to 1.390]; p = 0.0008) were associated with the use of regional anesthesia. Conclusion: In this single-institution retrospective study of adults who had undergone major open abdominal surgery for cancer, the use of regional anesthesia was not associated with race or ethnicity. In the multivariable analysis, age and female gender were associated with the use of regional anesthesia.